Immune cell crosstalk between ANCA-associated vasculitis and IgG4-related disease: an unresolved pathogenic link - Wang, Cui; He, Ronghua; Bai, Xue; Zhang, Yarui; Li, Jiawen; Zhao, Jie; Gao, Wenhui; Guo, Qiaoyan (Frontiers in Immunology, 2025)
Immunoglobulin G4-related disease (IgG4-RD) is a rare, multisystemic fibro-inflammatory condition affecting various organs, including kidneys, lungs, nasal cavity, pancreas, salivary glands, and orbit. Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAVs) is a multi-systemic inflammatory vascular disease encompassing eosinophilic granulomatosis with polyangiitis (EGPA), microscopic polyangiitis (MPA), and granulomatosis with polyangiitis (GPA). It often overlaps with the organs or tissues affected by IgG4-RD. Clinically, some individuals with IgG4-RD are ANCA-positive, while some with AAV exhibit elevated IgG4 levels or IgG4-positive plasma cell infiltration, making these conditions difficult to distinguish. Reports have documented cases of overlap syndromes involving IgG4-RD and AAV, highlighting shared pathogenic mechanisms that may include macrophages, B cells, CD4+T cells, and inflammatory cytokines. However, the pathophysiological mechanism underlying these overlap syndromes remains unclear. This review examines potential pathophysiological links between IgG4-RD and AAVs (GPA/MPA) overlap syndromes.